Cell wall metabolism during maturation, ripening and senescence of peach fruit - Brummell, David A (Journal of experimental botany, 2004)
Cell wall changes were examined in fruit of a melting flesh peach (Prunus persica L.) allowed to ripen on the tree. Three phases to softening were noted, the first of which began prior to the completion of flesh colour change and an increase in ethylene evolution. Softening in young mature fruit, prior to ripening, was associated with a depolymerization of matrix glycans both loosely and tightly attached to cellulose and a loss of Gal from all cell wall fractions. After the initiation of ripening, but before the melting stage, softening was associated with continuing, progressive depolymerization of matrix glycans. A massive loss of Ara from the loosely bound matrix glycan fraction was observed, probably from side chains of glucuronoarabinoxylan, pectin, or possibly arabinogalactan protein firmly bound into the wall and solubilized in this extract. An increase in the solubilization of polyuronides also occurred during this period, when softening was already well advanced. The extensive softening of the melting period was marked by substantial depolymerization of both loosely and tightly bound matrix glycans, including a loss of Ara from the latter, an increase in matrix glycan extractability, and a dramatic depolymerization of chelator-soluble polyuronides which continued during senescence. Depolymerization of chelator-soluble polyuronides thus occurred substantially after the increase in their solubilization. Ripening-related increases were observed in the activities of exo- and endo-polygalacturonase (EC 3.2.1.67; EC 3.2.1.15), pectin methylesterase (EC 3.1.1.11), endo-1,4-beta-glucanase (EC 3.2.1.4), endo-1,4-beta-mannanase (EC 3.2.1.78), alpha-arabinosidase (EC 3.2.1.55), and beta-galactosidase (EC 3.2.1.23), but the timing and extent of the increases differed between enzymes and was not necessarily related to ethylene evolution. Fruit softening in peach is a continuous process and correlated closely with the depolymerization of matrix glycans, which proceeded throughout development. However, numerous other cell wall changes also took place, such as the deglycosylation of particular polymers and the solubilization and depolymerization of chelator-soluble polyuronides, but these were transient and occurred only at specific phases of the softening process. Fruit softening and other textural changes in peach appear to have a number of stages, each involving a different set of cell wall modifications